El marketing y su incidencia en el posicionamiento de la heladería Poncho Rosa de la ciudad de Riobamba - Valdivieso Cevallos, María José (2024)
The present research work entitled Marketing and its impact on the positioning of the Poncho Rosa ice cream parlor in the city of Riobamba, whose main objective was to determine how marketing affects the positioning of the “Poncho Rosa” ice cream parlor in the city of Riobamba. In the investigation a quantitative methodology was used, that is to say, data was collected through a survey of 6 questions to the customers of the ice cream shop that we had as a sample a total of 190 people, the information obtained was tabulated generating statistical tables and graphs leading us to the results extracted from the source. Giving us as results quantitative data which were analyzed and interpreted and became qualitative data. The hypothesis raised in the research was verified with the Chi square test giving us a value of .975 which proves the incidence of the dependent variable marketing and the independent variable positioning. As a last point, thanks to the field research it was possible to obtain as results that the company has a null management in the different digital platforms which has not allowed it to reach more customers to achieve its positioning in the market and in the mind of the consumer for this very important marketing strategies were developed which when applied will be very helpful to obtain successful results and thus generate more revenue.